Women's Attitudes Toward Intimate Partner Violence in Ethiopia: The Role of Social Norms in the Interview Context. (July 2017) - Trott, Carlie D.; Harman, Jennifer J.; Kaufman, Michelle R.
This study draws on a social norms framework to examine the influence of interview context—specifically the presence of other women and men—on women's reported attitudes toward intimate partner violence (IPV) in Ethiopia, where IPV rates are among the highest in the world. The sample (16, 515 women, ages 15-49) was taken from Ethiopia's 2011 Demographic and Health Survey. Results showed the odds of women "justifying" IPV to be nearly twice as great when other women were present during the interview, and nearly half in the presence of men. Implications for more sensitive interview methodology are discussed.